Isolation, Characterization, and Identification Candidate of Probiotic Bacteria Isolated from Wadi Papuyu (Anabas testudineus Bloch.) a Fermented Fish Product from Central Kalimantan, Indonesia - Yulistia Budianti Soemarie; Tiana Milanda; Melisa Intan Barliana (International Journal of Food Science)
During the wadi fermentation process, some microorganisms can grow, including lactic acid bacteria (LAB), affecting the taste and texture of the final product. Some LAB strains are used as probiotics such as the Lactobacillus and Bifidobacterium groups. This study aimed at isolating, in vitro characterizing, and identifying microbial isolates from wadi papuyu (Anabas testudineus Bloch.). The stages started from sample collection, manufacture of wadi papuyu by fermentation for 8 days, isolation of bacteria from wadi papuyu, in vitro characterization, and identification of bacterial isolates with VITEK 2 Compact and PCR-sequencing methods 16S rRNA and 18S rRNA. The number of microbial colonies growing on MRS agar and MHA was 22 in total, while after purification and characterization it was observed only 4 different microbial isolates. Candidates are tested to determine whether they meet the criteria to be candidates for probiotic cultures. The in vitro testing of four isolates showed that they do not possess probiotic characteristics, especially in autoaggregation tests. Identification results using the VITEK 2 Compact method and 16S rRNA gene PCR-sequencing showed that of the 4 isolated strains, three were bacterial and one belonged to yeasts.